2017
DOI: 10.1177/0956462416686513
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rectal gonorrhoea and chlamydia on HIV viral load in the rectum: potential significance for onward transmission

Abstract: The aim of this study was to investigate the effect of asymptomatic rectal bacterial sexually transmitted infections (STIs) on rectal HIV viral load (VL). A prospective cohort study of HIV-positive men who have sex with men attending a tertiary centre in London, UK, for their routine HIV care was performed. Forty-two HIV-positive men who have sex with men were recruited between January and August 2014. In participants on antiretroviral therapy (ART), there was no significant difference in rectal VL in those wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Similar to prior work [ 35 , 36 ], we did not find an association between rectal or pharyngeal GC/CT and detectable plasma HIV RNA. Instead, we observed an association between urogenital GC/CT and a detectable viral load, particularly among TW/MSM.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to prior work [ 35 , 36 ], we did not find an association between rectal or pharyngeal GC/CT and detectable plasma HIV RNA. Instead, we observed an association between urogenital GC/CT and a detectable viral load, particularly among TW/MSM.…”
Section: Discussionsupporting
confidence: 90%
“…Our finding supports the confirmed efficacy of treatment as prevention seen among discordant gay couples with high STIs burden in the PARTNER and the Opposites Attract studies [22,23]. Data from a cohort of HIV-positive MSM in London also showed that the presence of asymptomatic rectal chlamydia and gonorrhoea was not associated with increased rectal HIV RNA in those fully suppressed on ART [24]. A recent systematic review and meta-analysis of 4607 HIV RNA measurements from 2835 individuals also did not find a statistically significant effect of STIs on HIV RNA among individuals on ART [12].…”
Section: Discussionsupporting
confidence: 81%
“…Davies et al . also assessed differences in rectal viral loads among MSM on ART with and without STIs . Among their 18 participants, they found no significant difference in rectal viral loads between those with and without STIs; all rectal viral loads from both STI groups were below the limit of detection .…”
Section: Discussionmentioning
confidence: 99%